Individually controlled noise reducing devices to improve IEQ in classrooms of primary schools - Zhang, Dadi (A+BE | Architecture and the Built Environment, 2020)
In recent decades, many indoor environmental quality (IEQ) related problems (such as noise, odour, overheating, glare…) in classrooms have been identified. The impact of IEQ in classrooms on school children has been thoroughly researched. Consequently, many studies have been carried out to attempt to improve the IEQ in classrooms. However, most of the IEQ-improvements were developed based on general requirements and ignored individual differences. No matter how advanced these improvements are, always some children keep being unsatisfied with the IEQ in their classrooms. Given the fact that different children have different IEQ perceptions, preferences, and needs, it makes more sense to control the IEQ in classrooms on the level of the individual rather than of the room. Only by doing this can the comfort, health, and ultimately performance of school children be improved. For this reason, this research explored the possibility of customizing IEQ in classrooms of primary schools in the Netherlands. This thesis addressed the following topics: –Current ways of controlling IEQ in classrooms and their effect on school children’s IEQ perception; – Individual preferences and needs of primary school children related to IEQ in classrooms; – Impact of the main IEQ problem on school children’s perception and performance; – Use of individually controlled devices to cope with the main IEQ problem in classrooms; – Children’s feedback on an individually controlled noise-reducing device. Several approaches were used to address these topics, including a field study, lab studies, computer simulations and a prototype study. In the spring of 2017, the indoor environment group conducted the field study in 54 classrooms of 21 primary schools in the Netherlands. 54 teachers’ questionnaire and 1145 children’s questionnaire were collected and analysed. The results of the field study provided insight into the current ways to control IEQ in classrooms, as well as the preferences and needs of children with respect to IEQ in their classrooms. Through a series of correlation analyses, the current ways to control IEQ, namely teachers’ IEQ-improving actions, were shown to be inefficient in improving children’s IEQ perceptions in classrooms, even though these actions were conducted based on children’s requests. Two possible explanations can be put forward. First, a teacher could only take one action to respond to one child at a time, therefore, another child’s request might have been ignored. Second, the options that teachers had to change the IEQ in classrooms were quite limited (for example, in most classrooms, opening windows was the only thing the teacher could do if children felt too hot in summer). It was, therefore, concluded that a more effective method to control the IEQ in classrooms is needed. To create a good learning environment for school children, it is important to know their perceptions, preferences, and needs concerning IEQ in their classrooms. The analyses of the 1145 children’s responses showed that different children within the same classroom could have different IEQ perceptions, preferences, and needs. Based on their IEQ perceptions, preferences, and needs and with the use of a twostep cluster analysis method, the children were grouped into six clusters (‘Sound concerned’, ‘Smell and Sound concerned’, ‘Thermal and Draught concerned’, ‘Light concerned’, ‘All concerned’ and ‘Nothing concerned’), with each a different profile was established. The analysis of the children’s responses also showed that 87% of the children were bothered by noise (mainly caused by themselves) in their classrooms. Therefore, noise was identified as the main problem in the classrooms studied. To get more insight in this main problem, a lab study was conducted in the spring of 2018 in which children were invited to participate in a listening task with different background sounds. The experiment was conducted in two chambers (acoustically treated chamber and untreated chamber) with different reverberation times (RTs) at the same time. Results of the two-way ANOVA analysis showed a significant interaction between the impact of sound type and sound pressure level (SPL) on children’s performance in the untreated chamber (RT = 0.3 s). Additionally, the t-test results showed that children performed significantly better in the untreated chamber than in the treated chamber (RT = 0.07 s). This indicated that a shorter RT is not always better, and it was recommended to also introduce a lower limit for the RT in classrooms to prevent over-damping. After the establishment of the main IEQ problem, namely noise, the next step of this research was searching for an effective way to address this problem. Because the use of individually controlled devices in offices has shown to be able to improve both the IEQ and the workers’ satisfaction rates, it was assumed that these devices can have a similar effect on children in classrooms. To get a preliminary understanding of this assumption, a series of computer simulations was therefore conducted to test the effect of an individually controlled device on noise reduction. By comparing the simulation results of these individually controlled devices with the conventional ways to reduce noise (namely acoustic ceiling tiles), it was seen that the individually controlled devices have the ability to provide better acoustics in terms of providing shorter RTs and higher speech transmission indices. Subsequently, a real individually controlled noise-reducing device (ICND) was prototyped and tested in a lab study during the summer and autumn vacation of 2019. This prototype was similar to the stimulated device. It looks like a large umbrella that hung above every child’s head. In this research, two identical prototypes were tested with more than 200 school children, whose feedback was collected through questionnaires. Children could control the device using a remote controller. The descriptive analysis of children’s answers indicated that most of them liked this device and wanted to have one in their classrooms. The content analysis elucidated the reasons for their choices: children liked this device mainly because of its appearance (they thought it looked funny/cool/nice), and they wanted to have it mainly because of its functionality (they thought it worked/helped/reduced noise). Additionally, the device’s noise reducing effect was confirmed by simulations and measurements. This study showed the potential of the ICND to create better acoustics for every school child, and resulted in clear recommendations to improve the prototype. To sum up, this research showed that school children differ in their IEQ preferences and needs and, based on that, classified them into six clusters. It also indicated that teachers’ actions could not effectively improve IEQ in classrooms, which paves the way for the need for individual control of IEQ in classrooms of primary schools. Then, an ICND was designed and tested to address the main IEQ problem in classrooms, namely noise. The results obtained from the simulations, measurements, and children’s feedback on the prototype of the ICND, indicated the feasibility of such devices in classrooms at primary schools. More research in real classrooms, however, is needed.